A8.18 Human CD141+ dendritic cells are present at the site of inflammation in arthritis and promote the inflammatory process via IFN lambda. (31st January 2014) - Ramos, M I; Ramwadhdoebe, T H; de Groot, R; Helder, B; Teunissen, M B M; van der Coelen, D; de Jong, E C; Tak, P P; Lebre, M C
Abstract : Background and Objectives: Dendritic cells (DCs) are a heterogeneous population of antigen-presenting cells, crucial for the initiation and regulation of adaptive immunity, but also critical for the maintenance of both central and peripheral tolerance. However, remarkably little is known regarding the distribution, phenotype, maturation status, and functional profile of migratory DC populations in inflamed tissues and in particular in chronic autoimmune diseases. In this study we aimed to characterise the DC subsets and the nature of their in situ functional profile at the site of inflammation in arthritis. Materials and Methods: Single-cell suspensions from paired peripheral blood mononuclear cells (PBMC), synovial fluid mononuclear cells (SFMC) and Lymph node (LN) samples were stained with DC surface markers and analysed by flow cytometry (FACS). Immunohistochemical and double immunofluorescent stainings were performed for identification of the different DC subsets (CD1c +, CD304 + and CD141 + DCs) IFN λ (IL-29) and IL-29-producing cells. IFN λ receptor (IL-28RA), IFN λ (both IL-28 and IL-29), CxCL10 gene expression (mRNA) in synovial tissue (ST) from RA and PsA patients, and CXCL10 induced by IL-29 in RA and healthy donor T cells was assessed by qPCR. IL-28RA protein expression levels on T cells was analysed by western blot. Results: We reported for the first time that CD141 + DCs, human homologues of mouse CD8 + a DCs, are present at the site of inflammation in arthritis. These cells were present in blood, synovial fluid and ST of RA and PsA patients, RA LNs and lesional skin from PsA patients. FACS analysis revealed that these cells are increased in SFMCs compared to paired PBMCs in RA and PsA. We showed that IFN-l1 (IL-29) and IFN-l2 (IL-28A) are expressed in RA and PsA ST both at mRNA and protein level. We identified CD141 + DCs, CD304 + DCs and CD31 + endothelial/monocytes as the major IL-29 producers in ST. We observed IL-28RA expression in RA and PsA ST and identified IL-28RA + T cells in close proximity with IL-29-producing cells in RA tissue suggesting a possible interaction. T cells upregulated CXCL10 gene expression upon stimulation with recombinant IL-29. Interestingly, IL-29-induced CXCL10 could be inhibited by blocking Jak/STAT pathway. Conclusions: Studying the role of different DCs subsets in autoimmunity might provide new insights for the understanding of the inflammatory process in arthritis. Targeting specific DC subsets rather than general DC depletion might be a new and effective therapeutic strategy in arthritis.